2014
DOI: 10.1063/1.4905447
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tungsten concentration on crystalline structure and perpendicular magnetic anisotropy of Co-W films

Abstract: In this study, Co-W thin films deposited by DC magnetron sputtering were demonstrated to be perpendicular magnetic anisotropic with large magnetocrystalline anisotropy energy (MAE). Thermodynamic calculations based on Miedema’s semi-empirical model have been used to estimate the phase in this binary alloy system. Based on the thermodynamic calculations results, a series of Co-W thin films were deposited on amorphous Ta underlayer with different tungsten concentrations. According to the X-ray diffraction result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…The driving force of fcc (100) to the hexagonal structure could be sought in the changes in the bulk dissolved species, i.e., carbon and tungsten. As mentioned above, bulk carbon favors the fcc structure, whereas the presence of bulk-dissolved tungsten in Co increases the tendency toward the hcp arrangement . The subtle chemical changes within the Co matrix shown in Figure may or may not be responsible for the formation of hexagonal islands.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The driving force of fcc (100) to the hexagonal structure could be sought in the changes in the bulk dissolved species, i.e., carbon and tungsten. As mentioned above, bulk carbon favors the fcc structure, whereas the presence of bulk-dissolved tungsten in Co increases the tendency toward the hcp arrangement . The subtle chemical changes within the Co matrix shown in Figure may or may not be responsible for the formation of hexagonal islands.…”
Section: Resultsmentioning
confidence: 85%
“…As mentioned above, bulk carbon favors the fcc structure, 21 whereas the presence of bulkdissolved tungsten in Co increases the tendency toward the hcp arrangement. 30 The subtle chemical changes within the Co matrix shown in Figure 5 may or may not be responsible for the formation of hexagonal islands. Alternatively, one can hypothesize that the surface carbon found in the c(2 × 2) structure acts as a surfactant, preventing the transformation of the fcc(100) structure to the more stable densely packed hexagonal phase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It was shown that the annealing of thin Co/W-layered systems manifests itself in the drastic change of their magnetic properties, as explained by intermixing and strong structural modification . In particular, at low temperatures and W concentrations, Co–W binary alloys have hcp symmetry and, in contrast to the pure hcp -Co phase, experience crystal lattice deformation that appears as a reduced crystal axis ratio c/a . , At high temperatures or when the tungsten concentration increases, the hcp phase in Co–W alloys is no longer dominant resulting in nanoscale compositional fluctuation due to the magnetically induced phase separation in Co–W films , and amorphous structure formation that at the same time leads to the fade out of spontaneous magnetization and a drastic decrease in coercive force . These arguments suggest constructing an as-deposited Co/W interface by replacing a Co monolayer with a disordered Co 3 W layer, and for the annealed up to T ann = 240 °C system, the interfacial Co and W layers are substituted by two atomic thick disordered Co–W alloy layers.…”
Section: Resultsmentioning
confidence: 99%
“…Однако в исследуемых объектах она не выявлена. В этой связи акцент целесообразно сделать на кристаллическую магнитную анизотропию, причем не в рамках ГПУ структуры, как, например, указывается в [23], а применительно к реально наблюдающейся ГЦК структуре. При этом можно полагать, что усиление перпендикулярной анизотропии, связанной с осью легкого намагничивания типа [111], при легировании происходит как за счет повышения текстуры типа (111), так и за счет увеличения константы кристаллической анизотропии.…”
Section: заключениеunclassified